Non-covalent functionalized hexagonal boron nitride nanoplatelets to improve corrosion and wear resistance of epoxy coatings. Issue 70 (12th September 2017) - Cui, Mingjun; Ren, Siming; Qin, Songlv; Xue, Qunji; Zhao, Haichao; Wang, Liping
Abstract : In the present study, a non-covalent method was employed to modify hexagonal boron nitride (h-BN) nanoplatelets via π–π interaction of amine-capped aniline trimer (AT), which resulted in a stable dispersion of h-BN nanoplatelets in organic solvents. Abstract : In the present study, a non-covalent method was employed to modify hexagonal boron nitride (h-BN) nanoplatelets through π–π interaction of amine-capped aniline trimer (AT), which resulted in a stable dispersion of h-BN nanoplatelets in organic solvents. Meanwhile, epoxy coatings containing different content of h-BN nanoplatelets were fabricated, and corresponding corrosion protection performance and wear resistance were investigated. Results showed that the 1.0 wt% h-BN/epoxy coating has better corrosion protection performance than other coatings, which was due to the good barrier properties from stably dispersed h-BN nanoplatelets and the passivating effect from AT. Besides, the addition of h-BN nanoplatelets also contributed to the improvement in wear resistance of epoxy the coating.